Respuesta :
Answer:
49 r^2 - 112 r + 64 thus A.
Step-by-step explanation:
Expand the following:
r (49 r - 112) + 64
r (49 r - 112) = r×49 r + r (-112):
-112 r + 49 r^2 + 64
r×49 r = 49 r^2:
Answer: 49 r^2 - 112 r + 64
Answer:
The answer to your question is: letter A. 49r² - 112r + 64
Step-by-step explanation:
This is a binomial perfect square
(7r - 8)²
Process
1.- Square the first term
(7r)² = 49r²
2.- Twice the product of the terms
2(7r)(-8) = 14r(-8) = -112r
3.- Square the second term
(-8)² = 64
4.- Order the result
49r² - 112r + 64